Piebaldism – portraits of hereditary character: a series of cases - de Almeida Corrêa Alfredo, Melissa [UNESP]; Holanda, Ingrid Rocha Meireles [UNESP]; Castro, Ivanka Miranda [UNESP]; Haddad, Gabriela Roncada [UNESP] (GN1 Sistemas e Publicacoes, 2024)
Piebaldism is a rare, autosomal dominant dyschromia characterized by circumscribed poliosis and triangular achromia in the frontal region in 90% of affected individuals, with no other systemic involvement. The incidence of dyschromia in this Dermatology Department, in a short space of time, and with plenty of images, motivated the presentation of this series of cases. We show two families with piebaldism, treated at the same Dermatology Department in 2021: the first family, with a mother and son presenting achromic macules on the trunk and poliosis in the frontal region since birth; the second family, with a grandmother, aunt, mother, and son showing the same characteristics described.
Piebaldismo – retratos do caráter hereditário: uma série de casos
Keywords: Genetic; Piebaldism; Pigmentation Disorders; Skin Diseases